Synergy in Mergers and Acquisitions: Typology, Life Cycles, and Value - Feldman, Emilie R.; Hernandez, Exequiel (Academy of Management Review, 2022)
Value in mergers and acquisitions (M&A) derives from the synergistic combination of an acquirer and a target. We advance the existing conceptualization of synergies in three ways. First, we develop...